Limosilactobacillus reuteri as an Adjuvant in the Treatment of Peri-implant Mucositis in Total Rehabilitation: An Exploratory Study - Parreira, Gonçalo J.G. (2024)
Objectives: Mechanical debridement is the traditional method for the treatment of peri-implant mucositis (P-im) and its success depends on the patient's correct oral hygiene. It is believed that probiotics may help by their ability to modulate the oral biofilm, resulting in anti-inflammatory and antibacterial plaque action. The aim of this study was to evaluate the adjuvant effect of the probiotic Limosilactobacillus reuteri (LR) in the mechanical treatment of P-im. Materials and methods: This exploratory study included 29 subjects with implant-supported total rehabilitation and P-im, divided into test (TG) and control (CG) groups, equally subjected to professional mechanical debridement, with the administration of a daily GUM PerioBalance lozenge for 30 days added to the TG. The modified Plaque Index (mPlI) modified Sulcus Bleeding Index (mBI) and pocket depth (PD) were evaluated before the intervention (baseline) and 6 and 10 weeks later. Statistical analysis: Parametric and nonparametric tests with 5% significance level were used in the statistical analysis, using IBM SPSS Statistics 27.0 software. Results: Both treatments resulted in reduced mPlI, mBI, and PD at 6 weeks; while from 6 to 10 weeks there was an increase in mPlI and mBI and maintenance of PD. Compared with baseline, differences were close to statistical significance in the reduction in PD at 10 weeks in the CG (p = 0.018), after Bonferroni correction, and statistically significant in the mPlI at 6 weeks in the CG (p = 0.004) and in the TG (p = 0.002) as well as at 10 weeks in the TG (p = 0.016). Comparing the groups in the postintervention assessments, no statistically significant differences were found. Conclusion: LR adjuvant mechanical treatment of P-im does not show a clear benefit compared with mechanical treatment alone, with both interventions achieving similar clinical results. Further prospective and long-term studies are needed.